PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN DAN PENGANGGURAN TERHADAP KEMISKINAN - Panggabean, Krisfive Yanti; Marlina Ekawaty (Journal of Development Economic and Social Studies, 2024)
Poverty is a global problem that is difficult to solve because of its very complex and multidimensional phenomena, not least in North Sumatra. That's why eradicating poverty is the first of the 17 Sustainable Development Goals (SDGs). This study aims to determine the influence of economic growth, education, unemployment and the Covid-19 pandemic on poverty in the district/city of North Sumatra in the period 2017-2022. The data type used is secondary data in the form of panel data covering 33 Districts/Cities of North Sumatra Province from 2017- 2022. The data analysis method used is panel data regression analysis with dummy variables assisted by e-Views10 software. The results of the study showed that economic growth and the Covid-19 pandemic had no significant effect, while education had a negative and significant effect, and unemployment had a positive and significant effect on the poverty level in the district/city of North Sumatra in 2017-2022. The poverty rate in North Sumatra has consistently decreased from year to year. The potential of education and open unemployment must be put to good use by the government in order to achieve low poverty levels in the 33 districts/cities of North Sumatra.